Prodrug strategies to overcome problems in drug therapy - Rautio, Jarkko (Henry Stewart Talks, 2022)
Introduction to the prodrug concept, Prodrugs for improved solubility, Prodrugs for improved absorption, Prodrugs for reduced toxicity, The prevalence of prodrugs, Challenges using prodrugs